2008
DOI: 10.1534/genetics.107.084988
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Gap Gene giant Has an Anterior Segment Identity Function Mediated Through disconnected and teashirt

Abstract: The C2H2 zinc-finger-containing transcription factors encoded by the disconnected (disco) and teashirt (tsh) genes contribute to the regionalization of the Drosophila embryo by establishing fields in which specific Homeotic complex (Hom-C) proteins can function. In Drosophila embryos, disco and the paralogous disco-related (disco-r) are expressed throughout most of the epidermis of the head segments, but only in small patches in the trunk segments. Conversely, tsh is expressed extensively in the trunk segments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…kni mutants exhibit deletions of adjacent abdominal segments, leaving only the termini and last abdominal segment intact ([34]). Flies lacking gt expression exhibit labial-T1 fusions and defects in abdominal segments 5-7 ([35], [36]). Several gap gene products act as morphogens ( e.g.…”
Section: Long Germ Embryogenesis: the Drosophila Paradigmmentioning
confidence: 99%
“…kni mutants exhibit deletions of adjacent abdominal segments, leaving only the termini and last abdominal segment intact ([34]). Flies lacking gt expression exhibit labial-T1 fusions and defects in abdominal segments 5-7 ([35], [36]). Several gap gene products act as morphogens ( e.g.…”
Section: Long Germ Embryogenesis: the Drosophila Paradigmmentioning
confidence: 99%
“…As March et al [ 45 ] pointed out, correlation between Hox genes and tio/tsh genes in the arthropod species they investigated must be different from that in Drosophila [ 45 ], and indeed, we could not find any conserved correlation between the expression patterns of Hox genes and tio/tsh in our research organisms either. Correlation between the Hox co-factor disconnected ( disco ) [ 43 , 64 ] and tio/tsh [ 61 ] does not appear to be conserved in panarthropods outside Drosophila either [ 36 , 52 ], this study), suggesting that the entire network of head versus trunk patterning downstream of tio/tsh in these arthropods is significantly different from that in Drosophila .…”
Section: Discussionmentioning
confidence: 93%
“…It has further been shown that tsh interacts with trunk Hox genes, and that it represses characteristics of anterior segments in the trunk, making it an essential factor of trunk identity [ 3 , 16 , 62 ]. Similarly, tsh is regulated by gap genes to specify segments [ 64 ], and is involved in providing leg-identity to trunk appendages [ 24 ]. In Drosophila , and its closest relatives, there is a second paralog of this gene, called tiptop ( tio ) [ 41 ] that shares some of the functions of tsh [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antp and abd-A are Drosophila HOX genes ( 88 ), while bxd is expressed directly upstream of and is known to directly influence the behavior of ubx , another HOX gene ( 89 ). Furthermore, both disco and eve regulate the localization or expression of HOX genes, conversely , salm and bab2 are directly regulated by HOX genes ( 90–93 ), while unc-4 is a homeobox-containing protein and a paralogue of the HOX genes with similar functions ( 94 ). Finally, both noc and pnr are critical for proper eye formation ( 95 , 96 ), grn has importance in multiple organ development ( 97 ) and immune response in the midgut ( 98 ), and zfh1 is essential to cell differentiation of lateral mesodermal derivative lineages and in neurogenisis ( 99 ).…”
Section: Resultsmentioning
confidence: 99%